Application and future perspective of CRISPR/Cas9 genome editing in fruit crops. Issue 3 (19th April 2019) - Zhou, Junhui; Li, Dongdong; Wang, Guoming; Wang, Fuxi; Kunjal, Merixia; Joldersma, Dirk; Liu, Zhongchi
Abstract: Fruit crops, including apple, orange, grape, banana, strawberry, watermelon, kiwifruit and tomato, not only provide essential nutrients for human life but also contribute to the major agricultural output and economic growth of many countries and regions in the world. Recent advancements in genome editing provides an unprecedented opportunity for the genetic improvement of these agronomically important fruit crops. Here, we summarize recent reports of applying CRISPR/Cas9 to fruit crops, including efforts to reduce disease susceptibility, change plant architecture or flower morphology, improve fruit quality traits, and increase fruit yield. We discuss challenges facing fruit crops as well as new improvements and platforms that could be used to facilitate genome editing in fruit crops, including dCas9‐base‐editing to introduce desirable alleles and heat treatment to increase editing efficiency. In addition, we highlight what we see as potentially revolutionary development ranging from transgene‐free genome editing to de novo domestication of wild relatives. Without doubt, we now see only the beginning of what will eventually be possible with the use of the CRISPR/Cas9 toolkit. Efforts to communicate with the public and an emphasis on the manipulation of consumer‐friendly traits will be critical to facilitate public acceptance of genetically engineered fruits with this new technology. Abstract : Fruits provide essential nutrients to human and are major economical drivers for many regions. With the CRISPR/Cas9 technology, fruit crops stand to gain tremendously in trait improvement. This review summarizes current progress, discusses challenges, and suggests areas of needed improvement in the application of this revolutionary technology to fruit crops.